On Boundary Value Problems with Implicit Random Non-Conformable Fractional Differential Equations - Bekada, Fouzia; Salim, Abdelkrim (Sarajevo Journal of Mathematics, 2024)
In this paper, we present some results on the existence, uniqueness and Ulam stability for a class of problems for nonlinear implicit random fractional differential equations with non-conformable derivatives. For our proofs, we employ some suitable fixed point theorems. Finally, we provide some illustrative examples.